Pragmatic Analysis of Jane Austen’s Pride and Prejudice (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research aims to analyze conversational features in pride and prejudice from cooperative principle of pragmatics. Various utterances have been analyzed in the novel with minute observation to figure out the contextual meaning of the dialogues. This study also helps us to analyze every character’s psycho-analytic perception. The contextual meaning has been traced by keeping in mind the background of the existing situation where the characters exchange the dialogues willingly and unwillingly. Jane Austen has given a dramatic touch to this novel with lots of dialogues exchanged among the characters. All chapters in the novel are included mutual conversations and they exchange properly. It deserves to do more justice with elements of pragmatics i.e. Cooperative principle by employing various maxims of CP. It can be seen, as the story unfolds, characters take strong positions and become a vital part of developing plot. Thus I have observed conversation between Mr. Darcy and Elizabeth, Mr. Bingley and Mr. Darcy, Mr. Bennet and Mrs. Bennet, Jane and Elizabeth etc. to have an eagle-eyed observation of the invisible meaning of various important conversations in different situations in the novel.